Cos5x-sin5x=sin7x-cos7x

Cos5x-sin5x=sin7x-cos7x
Гость
Ответ(ы) на вопрос:
Гость
Решение: cos5x-sin5x=sin7x-cos7x  cos5x+cos7x=sin5x+sin7x 2сos6x*cosx=2sin6x*cosx сos6x*cosx-sin6x*cosx=0 cosx(cos6x-sin6x)=0 a) cosx=0 x1=π/2+πn cos6x-sin6x=0 tg6x=1 6x=π/4+πn x2=π/24+πn/6
Гость
cos5x-sin5x=sin7x-cos7x  cos5x+cos7x=sin5x+sin7x 2сos6x*cosx=2sin6x*cosx сos6x*cosx-sin6x*cosx=0 cosx(cos6x-sin6x)=0 a) cosx=0 x1=π/2+πn cos6x-sin6x=0 tg6x=1 6x=π/4+πn x2=π/24+πn/6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы